Cover Picture: Energy and Exergy Analyses of a Pyroelectric‐Based Solar Energy Harvesting System (Energy Technol. 12/2015). Issue 12 (December 2015) - Sharma, Manish; Vaish, Rahul; Chauhan, Vishal Singh
Abstract : Solar Energy Pyromania: The cover picture illustrates the potential application of pyroelectric materials for solar energy harvesting. These pyroelectric materials can be used in solar photovoltaic (PV) panels to improve their efficiency. Rahul Vaish and colleagues at the Indian Institute of Technology Mandi have been exploring such possibilities. The backdrop image is a photograph of the campus of Indian Institute of Technology Mandi where the research was performed. More details can be found in the Full Paper by Sharma et al. (DOI:10.1002/ente.201500230 )